2022
DOI: 10.2196/32302
|View full text |Cite
|
Sign up to set email alerts
|

Media Source Characteristics Regarding Food Fraud Misinformation According to the Health Information National Trends Survey (HINTS) in China: Comparative Study

Abstract: Background Ongoing rumors and fake news regarding food fraud, adulteration, and contamination are highly visible. Health risk information circulating through media and interpersonal communication channels has made health crisis an important research agenda. Objective This study explored the issue of food fraud and the effect of misinformation. Further, it assessed whether and how these issues have provided evidence-based interventions for food handlers … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Data were collected in two Chinese cities: Beijing (the capital of China) and Hefei (a second-tier and capital city in Anhui Province). The target population was aged between 18 to 60 years [79]. In each city, respondents from urban and subsidiary rural areas were included.…”
Section: Samplingmentioning
confidence: 99%
“…Data were collected in two Chinese cities: Beijing (the capital of China) and Hefei (a second-tier and capital city in Anhui Province). The target population was aged between 18 to 60 years [79]. In each city, respondents from urban and subsidiary rural areas were included.…”
Section: Samplingmentioning
confidence: 99%
“…Additionally, even though it was not statistically significant, it is possible that some of the participants who used magazines and books as their main source of information would be more likely to prefer domestic products. As Chang et al. (2022) reported, fake news on food safety is not limited to interpersonal communication and the internet; it also pervades traditional media, including books and magazines, which are likely to include false information.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, even though it was not statistically significant, it is possible that some of the participants who used magazines and books as their main source of information would be more likely to prefer domestic products. As Chang et al (2022) reported, fake news on food safety is not limited to interpersonal communication and the internet; it also pervades traditional media, including books and magazines, which are likely to include false information. In particular, NFS 54,3 books, magazines (which sometimes contain sensational articles not necessarily based on scientific evidence) and informal conversations cannot be corrected quickly, even if they contain misinformation.…”
Section: Factors That Influence Consumers To Choose Domestic Foodmentioning
confidence: 99%
“…Thus, HINTS has been applied to various studies on cigarette smoking, cancer, food fraud, and HISB in the Chinese context. For instance, in 2022 Chang et al [48] used the HINTS to investigate individuals' preferences for health information channels and sources of health rumors among Chinese adults in mainland China. The study found that respondents preferred to visit their physicians for health information, whereas they primarily received health rumors through the internet, family members, and friends.…”
Section: Overviewmentioning
confidence: 99%
“…Participants were asked about their sources of health information and frequency of seeking health information. Nine information sources of 3 traditional media, including television, radio, and newspapers or magazines; 3 web-based media, including websites or search engines, social media, and health-related or news applications; and 3 interpersonal sources, including physicians or health specialists, family members, and friends or colleagues were measured [48]. Four-point frequency scales were used, ranging from 1 (never) to 4 (always).…”
Section: Hisb Measuresmentioning
confidence: 99%